The Relationship of the Muhadharah Program to improving Students’ Public speaking Skills at the Islamic Centre Al Quds of the Dewan Da’wah Sumatera Barat / Dampak Program Muhadharah terhadap Keterampilan Berbicara di Depan Publik Siswa di Islamic Centre Al-Quds, Dewan Dakwah Sumatera Barat - Hidayatullah, Muhammad Rizky; Saputra, Edi (Alhadharah: Jurnal Ilmu Dakwah, 2025)
This study examines the impact of the Muhadharah program on students’ public speaking skills at the Islamic Centre Al-Quds, West Sumatra. The topic highlights the importance of mastering oral communication skills for da’wah, academics, and career development, alongside the need to evaluate the program’s effectiveness. Using a quantitative correlational approach, data were collected from 22 active participants through a Likert-scale questionnaire and evaluation records. Data analysis employed Pearson correlation and simple linear regression. Results showed a positive and significant relationship between the Muhadharah program and students’ public speaking skills (r = 0.603; p = 0.003), with the program contributing 36.4% to skill improvement. These findings confirm that Muhadharah, as a practice-based training program, is effective in enhancing students’ communication abilities within Islamic educational settings.